Prospects for Artificial Intelligence Integration in the Transformation of Indonesia’s Legal Ecosystem - Ahmad Faiz Shobir Alfikri; Maziya Rahma Wahda; Ahmad Zulfi Wahyudi; M. Azam Rahmatullah (Presscience, 2026)
The adoption of artificial intelligence (AI) in the legal sector has driven a significant transformation in Indonesia’s legal ecosystem. This study addresses three research questions: (1) How has AI been adopted within Indonesia’s legal sector, and what forms does this adoption take? (2) What potential does AI hold for strengthening legal research, the legal profession, and judicial administration? (3) What regulatory framework is urgently required to govern AI use in Indonesia’s legal context, and how does it compare with existing international models? Employing a normative legal research methodology with conceptual and statutory approaches, this study conducts a prescriptive analysis of primary legal materials (statutes and regulations), secondary sources (academic literature and case studies), and comparative regulatory models, including the European Union’s AI Act. The findings reveal that AI adoption in Indonesia’s legal sector has progressed through private-sector platforms: Legal Hero, Legal Pro, and Allex, and through judicial innovation via the Supreme Court’s Smart Majelis system. While these developments demonstrate measurable efficiency gains, critical regulatory issues persist: no Indonesian statute directly governs AI’s specific characteristics, creating risks of algorithmic bias, erosion of judicial independence, opacity in decision-making, and data privacy violations. This study argues that Indonesia must adopt a risk-tiered, comprehensive AI regulatory framework, drawing on lessons from the EU AI Act while adapting to Indonesia’s socio-legal context, to ensure that AI strengthens rather than undermines the integrity of the national legal system.